PENDAMPINGAN PEMBUATAN POP-UP BOOK SEBAGAI MEDIA VISUAL PEMBELAJARAN TEMPAT DHARMAYATRA AGAMA BUDDHA UNTUK PEMBINA SEKOLAH MINGGU BUDDHA VIHARA WENING SARI - Supartono, Supartono; Budiadi, Seno; Yoga, Riko Arma; Bagaskara, Sukiman (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
Sekolah Minggu Buddha (SMB) plays a vital role in imparting Buddhist values to children and youth, yet traditional lecture-based methods often fail to engage students effectively. This community service project aimed to enhance learning at SMB Vimala Sari, Semarang, Indonesia, by developing an interactive Pop-Up Book titled "Exploring Dharmayatra Sites with Moka and Mona." The project was implemented in four sequential phases: (1) preparation and needs assessment, involving focus group discussions with teachers and a literature review on Buddhist pilgrimage sites such as Candi Borobudur and Candi Mendut; (2) training and mentoring, where teachers learned to create Pop-Up Books through workshops focusing on technical skills and age-appropriate content design; (3) evaluation and refinement, using surveys and interviews with teachers to assess the book’s impact; and (4) follow-up and sustainability, including train-the-trainer programs, exploration of digital formats, plans for mass production, and dissemination to other communities. The Pop-Up Book significantly improved student engagement and comprehension, enabling teachers to adopt more creative teaching strategies. The project successfully built internal capacity and provided a replicable model for educational innovation in religious settings. Recommendations for future development include regular content updates, enhancing teachers’ digital literacy, fostering inter-institutional collaborations, replicating the model in other SMBs, and conducting long-term impact evaluations